2018
DOI: 10.21837/pmjournal.v16.i5.431
|View full text |Cite
|
Sign up to set email alerts
|

Human Interdependency for Sustainable Well-Being: Structural Invariance Across Settlement Areas

Abstract: This survey research examined the underlying structure of subjective sustainable well-being (SSWB) discovered in the relationships of (i) Human Interdependence with other Humans (HIH), (ii) Human Interdependence with the Environment (HIE), and (iii) subjective well-being (SWB). The objectives of the empirical analysis were (i) to assess the causal relationship between human interdependence and SWB which instituted the SSWB structural model, and (ii) to evaluate the settlement areas-invariant of the causal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The human-nature connection measures the interrelationships between human and nature at individual level. Connections with nature is a vital groundwork of one's ecological behaviours (Abu Bakar et al, 2018). The benefits of humannature connection are delivered through human multisensory experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human-nature connection measures the interrelationships between human and nature at individual level. Connections with nature is a vital groundwork of one's ecological behaviours (Abu Bakar et al, 2018). The benefits of humannature connection are delivered through human multisensory experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of individuals functionality and contributions to their social and environmental contexts that in turn influence the well-being of the individuals is known as Human Interdependence [HI] (Abu Bakar et al, 2019a;2019b;2019c;Abu Bakar et al, 2020a;2020b;2020c). Detailed studies on HI found that HI predicts 70% of Subjective Well-Being, suggesting that a huge source of individual well-being exists in the course of imparting well-being to social and environment surroundings (Abu Bakar et al, 2015;2016a;2016b;2017a;2017b;2017c;2017d;2017e;2017f;2018). This paper focuses on Human Interdependence with the Environment [HIE].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human Interdependence [HI] measures the contributions and functionality of individuals in their social and environmental contexts that in turn influence the well-being of the individuals (Abu Bakar et al, 2019a;2019b;2019c;Abu Bakar et al, 2020a;2020b;2020c). Thorough studies on HI discovered that HI contributes to 70% of Subjective Well-Being, suggesting that that imparting wellbeing to social and environmental surroundings is a huge source of individual well-being (Abu Bakar et al, 2015;2016a;2016b;2017a;2017b;2017c;2017d;2017e;2017f;2018). This paper focuses on Human Interdependence with the Environment [HIE].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Waste separation, practising buyback centres and recycling and reusing household items (Zena et al, 2014) High income and education level favour the green movement and have concerns for food safety Purchasing and consuming organic food (Teng et al, 2011) Concern on solid waste management and readiness to adjust to new practices Bring reusable bag for shopping (Zen et al, 2013) Awareness (familiarity to energy-efficient labels), attitude (standpoint on energy-savings) and social norms (environmental lifestyles) Purchasing energy-efficient products and appliances based on energy efficiency labels (Zainudin et al, 2014) Perceived consumer effectiveness (environment related past experience behaviour, environment-related intentionbehaviour, willingness to pay, and regulatory support -separating household waste, being a member of environmental groups environmentally conscious consumer behaviour (purchasing biodegradable products, energysaving products, and products that are less harmful to the environment) (Ramly et al, 2012) Environmental emotions, environmental cognition (well-informed, understanding and knowledge on green practices), environmental attitude (general sense of favourableness or unfavourableness for green behaviour) Keeping materials out of the waste stream: reduce (minimising consumption), reuse (use again or repurpose used materials) and recycle (Nameghi & Shadi, 2013) The case studies generated three significant components of AP: (i) Energy Saving (APa), (ii) Waste Handling (APb) and (iii) Smart Consumer (APc). Personal Lifestyle (PL) manifests in the personal outlook and approach to life in relation to environmental consciousness (Abu Bakar et al, 2017aBakar et al, , 2017bBakar et al, , 2017cBakar et al, , 2018. Qualities adhere to PL include (i) moral stance in collectivistic values (Laurens, 2012;Clark et al, 2014;Caesar, 2016), (ii) commitment to modest and environmental choices (Horayangkura, 2012;Laurens, 2012;Khare, 2015;Ming et al, 2015), and (iii) environmental concerns through knowledge and awareness (Horayangkura, 2012;Masud et al, 2013;Ming et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…HIE is one of the main causes of subjective sustainable well-being (SSWB). Personality and lifestyle (PL) and attitude and pro-environmental behaviours (AP) are interrelated dimensions of HIE (Abu Bakar et al, 2017aBakar et al, , 2017bBakar et al, , 2017cBakar et al, , 2018), yet the impact of specific PL items on AP has limited proofs. This paper assesses the statistical predictability of AP based on PL items of Malaysian respondents.…”
Section: Introductionmentioning
confidence: 99%